2019
DOI: 10.1055/a-0841-9831
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic partial reversal of complicated single anastomosis gastric bypass

Abstract: Endoscopic partial reversal of complicated single anastomosis gastric bypass needle puncture from gastric pouch into excluded stomach under EUS guidance. c 15 × 10 mm Hot Axios (Boston Scientific, Marlborough, Massachusetts, USA) lumen-apposing metal stent (LAMS) inserted to create gastro-gastric anastomosis. E-Videos E108Chang Jasmine Hui Er et al. Endoscopic partial reversal of gastric bypass … Endoscopy 2019; 51: E108-E110

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, no data regarding late complications including marginal ulceration was reported during their study period. Chang et al [26] had demonstrated the feasibility of endoscopic partial reversal of MGB-OAGB by creating a GG anastomosis with the insertion of a lumen-apposing metal stent. This endoscopic technique was performed in a patient who experienced severe malnutrition requiring enteral feeding through a gastrostomy tube.…”
Section: Revision To Sleeve Gastrectomymentioning
confidence: 99%
“…However, no data regarding late complications including marginal ulceration was reported during their study period. Chang et al [26] had demonstrated the feasibility of endoscopic partial reversal of MGB-OAGB by creating a GG anastomosis with the insertion of a lumen-apposing metal stent. This endoscopic technique was performed in a patient who experienced severe malnutrition requiring enteral feeding through a gastrostomy tube.…”
Section: Revision To Sleeve Gastrectomymentioning
confidence: 99%